Progress in the Characterization of the Surface Species in Activated Carbons by means of INS Spectroscopy Coupled with Detailed DFT Calculations. (17th September 2015) - Piovano, Andrea; Lazzarini, Andrea; Pellegrini, Riccardo; Leofanti, Giuseppe; Agostini, Giovanni; Rudić, Svemir; Bugaev, Aram L.; Lamberti, Carlo; Groppo, Elena
Abstract : Activated carbons are materials with relevance in different industrial applications. Due to the inherent complexity and heterogeneity of their structures, an easy assignment of the species present on their surface has a challenging result. Only recently, with the possibility to collect well-resolved inelastic neutron spectra and to simulate by DFT methods more or less extended graphitic clusters, this task is starting to become feasible. Here we report our investigation on a steam activated carbon and we show that different vibrations in the region of out-of-plane C-H bending modes are specifically connected to hydrogen terminations belonging to extended and regular borders or to short and defective ones. Furthermore, simulations including heteroatoms such as oxygen allowed us to point out spectral regions with a contribution from carboxyl species.